# By Remainder Theorem find the remainder, when p(x) is divided by g(x), where p(x) = x³ - 2x² - 4x - 1, g(x) = x + 1

**Solution:**

Given, p(x) = x³ - 2x² - 4x - 1

g(x) = x + 1

We have to find the remainder by __remainder theorem__ when p(x) is divided by g(x).

The __remainder__ theorem states that when a polynomial f(x) is divided by a __linear polynomial__ , x−a, the remainder of that division will be equivalent to f(a).

Let g(x) = 0

x + 1 = 0

x = -1

Substitute x = -1 in p(x) to get the remainder,

p(-1) = (-1)³ - 2(-1)² - 4(-1) - 1

= -1 - 2(1) + 4 - 1

= -1 - 2 + 3

= -3 + 3

= 0

Therefore, the remainder is 0.

**✦ Try This: **By Remainder Theorem find the remainder, when p(x) is divided by g(x), where p(x) = 3x³ - 6x² - 12x - 3, g(x) = x + 1

**☛ Also Check: **NCERT Solutions for Class 9 Maths Chapter 2

**NCERT Exemplar Class 9 Maths Exercise 2.3 Problem 14(i)**

## By Remainder Theorem find the remainder, when p(x) is divided by g(x), where p(x) = x³ - 2x² - 4x - 1, g(x) = x + 1

**Summary:**

By Remainder Theorem the remainder, when p(x) is divided by g(x), where p(x) = x³ - 2x² - 4x - 1, g(x) = x + 1 is 0

**☛ Related Questions:**

- By Remainder Theorem find the remainder, when p(x) is divided by g(x), where p(x) = x³ - 3x² + 4x + . . . .
- By Remainder Theorem find the remainder, when p(x) is divided by g(x), where p(x) = 4x³ - 12x² + 14x . . . .
- By Remainder Theorem find the remainder, when p(x) is divided by g(x), where p(x) = x³ - 6x² + 2x - . . . .

visual curriculum